A case of isolated cutaneous myeloid sarcoma preceding acute myeloid leukemia and literature review - Konstantina Mavridou; Sofia Gavriil; Alexandra Papoudou-Bai; George Gaitanis; Alexia Piperidou; Ioannis D. Bassukas (PAGEPress Publications, 2024)
Isolated Cutaneous Myeloid Sarcoma (icMS) and Aleukemic Leukemia Cutis (ALC) are cutaneous extramedullary manifestations of leukemia in which leukemic cells infiltrate the skin before they can be identified either in the peripheral blood or in the bone marrow. We report the case of a 67-year-old patient who presented with a rapidly developing cutaneous tumour and scaly, erythematous-squamous plaques. Isolated Cutaneous Myeloid Sarcoma was diagnosed which rapidly progressed to terminal-stage Acute Myeloid Leukemia (AML). To highlight the disease characteristics of the adult-onset icMS and ALC cases that preceded AML we additionally compiled the pertinent literature of case reports of these rare conditions. We identified n=15 previously published icMS/ALC cases with adequately detailed clinical data descriptions. We could confirm the medical experience that icMS/ALC patients have an overall worse prognosis. Moreover, we could identify FAB M5 AML subtype as a significant adverse prognosticator of these patients.